Food Insecurity Is Associated with Low Adherence to the Mediterranean Diet and Adverse Health Conditions in Portuguese Adults - Gregório, Maria João; Rodrigues, Ana M.; Graça, Pedro; de Sousa, Rute Dinis; Dias, Sara S.; Branco, Jaime C.; Canhão, Helena (Frontiers in Public Health, 2018)
Background: Food insecurity is a limited or uncertain access to the adequate food and is a significant public health problem. We aimed to assess determinants of food insecurity and the corresponding health impact in Portugal, a southern European country that faced a severe economic crisis. Methods: Data were derived from the Epidemiology of Chronic Diseases Cohort Study (EpiDoC), a population-based cohort of 10,661 individuals that were representative of the Portuguese adult population and followed since 2011. A cross-sectional analysis of the third wave of evaluation (EpiDoC 3) was performed between 2015 and 2016. Food insecurity was assessed with the household food insecurity psychometric scale. Socioeconomic, demographic, lifestyle, adherence to Mediterranean diet, self-reported non-communicable disease, health-related quality of life (HRQoL) (EQ-5D-3L), physical function (HAQ score), and health resource consumption information was also collected. Results: The estimated proportion of food insecurity was 19.3% among a total of 5,653 participants. Food insecure households had low adherence to the Mediterranean diet (OR=0.44; 95%IC 0.31–0.62). In addition, diabetes (OR=1.69; 95% IC 1.20–2.40), rheumatic disease (OR= 1.67; 95% IC 1.07–2.60), and depression symptoms (OR=1.50; 95% IC 1.09–2.06) were independently associated with food insecurity. On average, food insecure households had a lower HRQoL (OR=0.18; 95% IC 0.11–0.31) and a higher disability (OR=2.59; 95% IC 2.04–3.29). A significantly higher proportion of food insecure households reported being hospitalized (OR=1.57; 95% IC 1.18–2.07) and had more public hospital medical appointments (OR=1.48; 95% IC 1.12–1.94) in the previous 12 months. Conclusions: We found that food insecurity is highly prevalent in Portugal. Food insecurity was associated with low adherence to the Mediterranean diet, non-communicable chronic diseases, lower quality of life, and higher health resource consumption. Therefore, this study provides valuable insight into the relationship between food security and the diet and health of the population during an economic crisis.